Left Ventricular Aneurysm and Ventricular Septal Defect Following Myocardial Infarction: A Dangerous Cocktail - Assili, Hala El; Eddhima, Zaidane; Britel, Driss; Faliouni, Hicham; Bourzine, Nadia; Lakhal, Zouhair; Benyass, Aatif (RA Journal of Applied Research, 2021)
An ischemic ventricular septal defect (VSD) is a lethal complication of myocardial infarction (MI), commonly from 24 hours to up to 5 days of presentation with AMI. Despite the improvement of surgical techniques, the mortality is still very high with poor prognosis. Left ventricular aneurysm (LVA) may also be a fatal mechanical complication of MI but rarely occurs in the posterior or inferior portion of the interventricular septum. Concomitant AMI mechanical complications in the same patient are less than infrequent with poor prognosis, particularly with late hospital arrival. We present an unusual case of post-myocardial infarction ventricular septal rupture (PI-VSR) combined with left ventricular inferior/inferoseptal aneurysm that was managed surgically. The aim of this article is to make clinician alerted in case of mechanical complication, especially when post-MI patients become hemodynamically unstable with refractory congestive heart failure.